ANALISIS PENERAPAN FATWA DSN-MUI NO.108 TAHUN 2016 PADA PENGELOLAAN HOTEL SYARIAH DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Wulandari, Astrika; Lawang, Hasanna; Akil, M; Raehana, Syarifa; Subaedah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the suboptimal implementation of sharia principles in the hotel industry, despite the continued development of the sharia hotel concept in Indonesia. This phenomenon indicates a gap between claims of being a sharia hotel and operational implementation in accordance with Islamic economic law. Therefore, this study aims to analyze the implementation of DSN-MUI Fatwa No. 108 of 2016 concerning Guidelines for Organizing Tourism Based on Sharia Principles in the management of Al-Badar Hotel Syariah Makassar, and to identify various obstacles encountered in its implementation. The research method used is field research with a qualitative interpretative approach. Data collection techniques were carried out through in-depth interviews, direct observation, and documentation. The data obtained were then analyzed qualitatively with an inductive approach to understand the suitability between hotel management practices and the principles of sharia economic law. The results of the study indicate that the implementation of sharia principles has been carried out in several key aspects, namely service, facilities, and guest selection. In the service aspect, Islamic moral values ​​have been applied through the friendly and polite attitude of employees. In terms of facilities, the hotel has provided an environment free from haram elements and supports religious needs. Meanwhile, in terms of guest selection, the hotel has implemented a policy of refusing non-mahram couples. However, this implementation remains partial due to the lack of institutional support, such as the absence of a Sharia Supervisory Board (DPS) and the lack of a comprehensive sharia management system. The main obstacles faced include limited understanding of human resources, low public literacy regarding the concept of sharia hotels, and the absence of a formal oversight system. Therefore, this study recommends strengthening institutions and improving human resource competencies to optimize the implementation of sharia principles comprehensively and sustainably.